Analysis of Social Influence, Influencer Credibility, and Parasocial Relationships on Brand Credibility and Purchase Intention of Fashion Products on The Instagram Platform - Aulia Galuh Bagjamaghfira; Ujang Sumarwan; Nur Hasanah (Green Publisher Indonesia, 2025)
The rise of social media, particularly Instagram, has transformed consumer behavior and marketing strategies in the fashion industry. This study aims to analyze the influence of social influence, influencer credibility, and parasocial relationships on brand credibility and purchase intention of fashion products on Instagram. Using a quantitative approach with a cross-sectional survey method, data were collected from 260 active Instagram users in Greater Jakarta who follow at least one fashion influencer. Structural Equation Modeling with the Partial Least Squares (PLS) approach was employed to examine the relationships between variables. The results indicate that influencer credibility, social influence, and parasocial relationships have a significant positive effect on brand credibility, which in turn influences purchase intention. Parasocial relationships also directly enhance purchase intention. These findings highlight the crucial role of emotional connection and perceived credibility in shaping consumer behavior on social media. The study provides practical implications for fashion marketers in selecting influencers and developing engagement strategies to boost brand trust and consumer intention to purchase. Further research is suggested to explore other social platforms and additional influencing variables.